Implementation of Digital Business in Maximizing Small and Medium Enterprises During the Covid 19 Period - Aggy Pramana Gusman; Ahmad Vajri Rahman (KPN Kopertis X, 2022)
The SME products produced by the women's savings and loan cooperatives in Lubuk Basung, Agam Regency, West Sumatra are the majority of food products which are homemade on a home scale and are done by housewives. The growth and development of SMEs in the range of Maninjau Lake, Lubuk Basung, Agam Regency, especially those produced by housewives, has experienced various kinds of obstacles so that it is not optimal. Technology-based marketing strategies can be a major force to boost sales of these products. The purpose of this activity is to increase market share so as to increase turnover and profit from product sales through social media as a marketing tool for SME products. The number of participants was 47 people, consisting of housewives who were members of the cooperative. The method used is training and mentoring. The result of this training is an increase in the knowledge and ability of participants in the use of social media as a marketing tool, as indicated by a change in the average pretest and posttest scores, from a score of 71.03 to a score of 120.30. Participants' final understanding of social media Facebook is 70% greater than participants' final understanding of Instagram by 55%.